The blue shifts of the C-H and N-H bonds in the complexes of CHX3 (X = F, Cl, Br) and HNO: a theoretical study - Trung, Nguyen Tien; Hue, Tran Thanh (Vietnam Journal of Chemistry, 2014)
All calculations were performed at the high level of theory (MP2/6-311++G(d,p)). Five separate minima were identified on the potential energy surface of each complex pairing CH3X with HNO. In general, strength of complexes increases in going from F to Cl to Br, which is consistent with respective decrease of deprotonation enthalpy of the C-H bond respectively. All the C-H and N-H bonds are shortened upon complexation, corresponding to increase in their stretching frequencies. It is interesting that blue shift is observed in the N-H bonds; such a contraction in the N-H covalent bond is extremely rare. Linear correlation between change of stretching frequencies and change of the N-H and C-H bond lengths in all complexes has been reported in equation (1) and (2). Besides, the change of the N-H bond lengths and their stretching frequencies as a function of the change of occupation of σ*(N-H) orbitals and that of s-character of N hybrid orbitals were obtained as in expression (3) and (4).